Fonti di Weltliteratur Ungheria - Tottossy, Beatrice (Strumenti per la didattica e la ricerca, 2012)
53 writers invited to speak, as artists, of themselves and their world at the beginning of the new millennium in no more than 2002 keystrokes. A new research criterion with which Fonti di Weltliteratur. Ungheria obtains the real and literary data for a theoretical specification of the state and behaviour of the cultural sphere in the globalized context, in the critical passage constituted - for the political and economic spheres as well - by a transformation of linguistic-national realities. Brief historical notes on the recent and current status of the writer in a Hungary passing from dictatorship to democracy in the end enable light to be thrown on the possible fate of the general figure of the intellectual in the perspective of the realization of a Goethean Weltliteratur. Fonti di Weltliteratur. Ungheria by Beatrice Töttössy is licensed under a Creative Commons Attribuzione-Non commerciale-Non opere derivate 2.5 Italia License.Based on a work at www.fupress.com.